Prevalence of complications of Type 2 Diabetes Mellitus and its association with different risk factors in Urban Etawah, Uttar Pradesh - Sachan, Neha; Srivastava, Dhiraj Kumar; Jain, Pankaj; Singh, Santosh Kumar; Mahima,; Shukla, Sushil Kumar (Indian Journal of Community Health, 2021)
Background- India is experiencing a rapid health transition, with large and rising burdens of chronic diseases, which were estimated to account for 53% of all deaths in 2005. Earlier estimates projected that the number of deaths attributable to chronic diseases would rise from 3·78 million in 1990 (40·4% of all deaths) to 7·63 million in 2020 (66·7% of all deaths). Aims and Objectives- To find out the prevalence of Complications of Type 2 Diabetes Mellitus and its association with different risk factors in Urban Etawah (U.P.) including tobacco, alcohol, fatty meals and physical activity. Material and Methods- The present study is a community-based study performed among 400 participants using cluster sampling technique in the field practice area of Urban health training centre, Department of Community Medicine, UPUMS, Saifai, Etawah. The participants were interviewed using a pre-tested questionnaire using Diabetes Complication Index. Results- Among the diabetics, the prevalence of coronary heart disease (CHD), peripheral vascular disease (PVD), cerebrovascular accidents (CVA), cataract, neuropathy and foot problems were 24%, 24%, 7%, 15.4%, 38%, 26% and 2% respectively. A statistically significant association was seen with fatty meals and complications. Conclusion - All the diabetic complications observed need to be addressed in prevention and control strategies in the study area. Heath screening camps will be organized for the people for awareness.